Physical Characteristics of the I Type and II Type Crystal of Rifampicin - Chao, Liu; Chao, Wang; Maixi (Asian Journal of Chemistry, 2012)
In this paper, the physical characteristics of the I type and II of rifampicin are reported. Some analytical methods as were adopted viz., FT-IR, X-ray powder diffraction, DSC, SEM and NIR to characterize the rifampicin crystals.